2005
DOI: 10.1097/00008469-200502000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Milk/dairy products consumption, galactose metabolism and ovarian cancer: meta-analysis of epidemiological studies

Abstract: Ovarian cancer is the fifth most common cause of cancer death among women and the leading cause of gynaecological cancer death in the United States. Milk/dairy products consumption was considered to be a risk factor for ovarian cancer mainly because milk carbohydrate-lactose and galactose metabolism is toxic to oocytes. However, recent evidence does not support this hypothesis completely. We collected epidemiological studies related to the association between milk/dairy products consumption or galactose metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
2
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 51 publications
4
20
2
4
Order By: Relevance
“…In fact, the fixed effects and the random effects provide similar results across homogenous studies. The detailed calculation formulas have been described in our previous study ( 11 ). The results of meta-analysis may be biased if published studies are dependent on results.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the fixed effects and the random effects provide similar results across homogenous studies. The detailed calculation formulas have been described in our previous study ( 11 ). The results of meta-analysis may be biased if published studies are dependent on results.…”
Section: Methodsmentioning
confidence: 99%
“…In 1990, Mettlin and Piver suggested that it was not the lactose content of milk but rather its fat content that was responsible for the association. High consumption of fat may influence ovarian cancer risk through increased oestrogen levels (Qin et al, 2005). Since this effect was absent for serous ovarian cancer, we hypothesise that dairy fat may present a risk for ovarian cancers other than serous, such as the endometrioid subtype, but their small number (n ¼ 24) did not allow for separate analysis.…”
Section: Dairy Consumption and Ovarian Cancer M Mommers Et Almentioning
confidence: 99%
“…The results from case -control and prospective cohort studies regarding milk consumption and ovarian cancer risk have been inconsistent (Mettlin and Piver, 1990;Webb et al, 1998;Kushi et al, 1999;Cramer et al, 2000;Goodman et al, 2002;Fairfield et al, 2004;Larsson et al, 2004;Qin et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the notion that dairy food consumption increases the risk of ovarian cancer has been highly controversial and, currently, the role of galactose has not been shown (72)(73)(74)(75)(76)(77).…”
Section: Effect Of Milk and Dairy Foods On Diseasementioning
confidence: 99%